Risk factors for early death in urgent‐start peritoneal dialysis patients: A multicenter retrospective cohort study. Issue 5 (27th December 2021) - Meng, Lingfei; Yang, Liming; Zhu, Xueyan; Sun, Zhanshan; Zhang, Xiaoxuan; Li, Xinyang; Cheng, Siyu; Guo, Shizheng; Zhuang, Xiaohua; Zou, Hongbin; Luo, Ping; Cui, Wenpeng
Abstract: Background: Assess risk factors for early death in patients who underwent urgent‐start peritoneal dialysis (USPD). Methods: Patients who initiated USPD in five peritoneal dialysis centers from 2013 to 2019 were screened in this multicenter retrospective cohort study. Risk factors for all‐cause mortality within 3 months were explored. Results: A total of 1265 USPD patients with 43 early deaths were included. Cox regression analyses showed that age older than 60 years (hazard ratio [HR], 3.054; 95% CI [1.597, 5.842]; p = 0.001), albumin less than 30 g/L (HR, 2.234; 95%CI [1.207, 4.136]; p = 0.011), blood glucose greater than 7 mmol/L (HR, 2.766; 95%CI [1.477, 5.180]; p = 0.001), higher estimated glomerular filtration rate (eGFR; HR, 1.121; 95%CI [1.071, 1.172]; p = 0.000), and poor stages of heart failure (class IV compared with class 0‐I; HR, 5.165; 95%CI [2.544, 10.486]; p = 0.000) were independent predicting factors for early death. Conclusions: Risk factors for early death were older age, hypoproteinemia, hyperglycemia, higher eGFR, and severe heart failure.